Specificity of Teaching Conductors and Choral Disciplines in the Training of Future Teachers of Music Art - Vasilyeva, Oksana; Sokolova, Alla (Professional Art Education, 2021)
The purpose of the article is to determine the specifics of teaching conducting and choral discipline in the process of the professional training of future music art teachers; to identify the main directions of vocal and choral work at school choral singing as a type of collective musical activity on music lessons and ruling school choirs and vocal ensembles in extracurricular time).The study characterizes the peculiarities of teaching such basic disciplines of the conductor-choir cycle as Choral Conducting, Choral Arrangement, Choral Studies, Choral Class, Workshop on «Workshop of working with a choir».The main tasks of the disciplines are outlined as follows: mastery of conducting and choral knowledge, development of professional musical abilities, formation of teacher-choirmaster skills. The study of the problem proved the need to focus the content of conducting and choral disciplines on the peculiarities of the music art teacher activities. These should include learning song repertoire for children's choirs; mastering arranging skills for children's singing groups of different age categories; acquiring the knowledge of the development and protection of children's voice, as well as methods of vocal and choral work with children in secondary education.
Keywords: conducting and choral disciplines; music art teacher; choral conducting; choral class; choral studies; choral arrangement